Islamic Dialectics and the Science of Rationality in the Perspective of Islamic Educational Philosophy - Latipah, Euis; Murojab, Muhammad; Habibah, Siti Nurhasanah; Purwanti, Neng Yayu; Khoirunnisa, Yuni (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This article examines the dynamic relationship between Islam and the science of rationality in the perspective of Islamic educational philosophy, focusing on the dialectics formed in the development of educational concepts and practices. A philosophical approach is used to analyze the interaction of the two elements, revealing how Islamic values can synergize with the principles of scientific rationality to build a balanced, relevant, and transformative educational paradigm. This research is based on a qualitative analysis method, by integrating various primary and secondary sources. The results of the study show that the collaboration between Islamic spirituality and scientific rationality is able to encourage more progressive educational innovation while building awareness of the importance of knowledge as part of religion. This emphasis on integration makes a significant contribution to creating an education system that is holistic, contextual, and oriented towards universal human values.